Pembingkaian Berita Data Korban Gempa Cianjur 328 Tewas Pada Media Kompas.Com Dan Detik.Com - Dimas Putra Hermawan; Hendra Setiawan (Peneliti.net, 2023)
Earthquakes are natural disasters that have claimed many lives, one of which is the Cianjur earthquake which has claimed many lives. The media is one of the fastest sources of information so that the news about this earthquake has been widely covered by well-known news media. One of them is detik.com and Kompas.com. This media news presents actual information and has its own characteristics, so this research is made to analyze the two media from the same news. The analysis of this study uses the theory of Framing Analysis using the zhongdang Pan and Gerald M Kosicki models. In this study using a qualitative approach. Data collection techniques are carried out by collecting some data results from an online media. The results of Zhongdang Pan Kosicki's framing analysis for these two media have complete elements of syntax, script, and thematic. But for rhetorical elements these two news have metaphors. The characteristics of these two media are also different. Detik.com has many opinions and repetitions of the previous successive news, while Kompas.com shows leading information and immediately reveals the news